Post-Approval Changes in Pharmaceuticals: Regulatory Perspectives in Europe - Kumar, Pankaj; Yadav, Vibhu; Kaushik, Deepak (Applied Clinical Research, Clinical Trials and Regulatory Affairs, 2015)
Post approval changes are an integral part of pharmaceutical product life cycle management. These changes need to be carefully monitored and must follow proper regulatory path of given jurisdiction. The present work identifies the post approval changes, policies, guidelines and procedure for submission of post approval changes in Europe. The European medical agency (EMA) in their several guidelines has clearly defined the regulatory framework for post approval changes which are known as variation filing in Europe. The article further describes the types of changes, categorization and procedure for the submission of variation changes. In Europe, variations are classified as Type-IA for minor changes, Type-IB for moderate changes and Type-II for major changes. These minor changes can be implemented without an approval from the agency but should be reported and the major changes needs an approval letter from the agency. The case study on the product Humalog (insulin lispro) has been described to obtain better understanding of post approval changes in Europe.
Keywords: Centralised procedure